2001
DOI: 10.1097/00000539-200112000-00019
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Determining Trial of Heparinase-I (Neutralase™) for Heparin Neutralization in Coronary Artery Surgery

Abstract: Heparinase-I (Neutralase(TM)) successfully restored activated coagulation time with no adverse hemodynamic events in patients undergoing coronary artery surgery with cardiopulmonary bypass in an open-label dose-determining trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Heparinase I, a specific enzyme that inactivates heparin, is another possible alternative to protamine (Michelsen et al 1996). Heres et al (2001) found that heparinase-I successfully restored activated coagulation time with no adverse hemodynamic events in patients undergoing coronary artery surgery with cardiopulmonary bypass in an open-label dose-determining trial. Finally, heparin-binding filters have been also considered as an alternative to protamine but additional human studies are needed to demonstrate the safety and efficacy of the method (Ma et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Heparinase I, a specific enzyme that inactivates heparin, is another possible alternative to protamine (Michelsen et al 1996). Heres et al (2001) found that heparinase-I successfully restored activated coagulation time with no adverse hemodynamic events in patients undergoing coronary artery surgery with cardiopulmonary bypass in an open-label dose-determining trial. Finally, heparin-binding filters have been also considered as an alternative to protamine but additional human studies are needed to demonstrate the safety and efficacy of the method (Ma et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…25f, 43 Early clinical trials demonstrated that a single intravenous injection of recombinant heparinase-I (Neutralase) could dose-dependently neutralize anticoagulant heparin in heart surgery patients. 44 However, later trials were terminated due to ineffectiveness and safety concerns. Endosulfatases are important enzymes that edit the sulfated domains of HS by removing the 6- O -sulfate groups.…”
Section: Targeting Heparan Sulfate-protein Interactionsmentioning
confidence: 99%
“…When given in doses up to 30 μg/ kg, heparinase I successfully neutralized heparin's anticoagulant effect in a dose-dependent fashion without significant adverse sequelae. Heres et al (2001) assessed the heparinneutralizing activity and safety profile of different doses of heparinase I in 49 patients undergoing coronary artery surgery. They found that heparinase I, 7 or 10 μg/kg, effectively restored the ACT after unfractionated heparin was given to patients undergoing CPB for coronary artery surgery.…”
Section: Heparin Antagonistmentioning
confidence: 99%